Canadian dentists’ awareness and views on early childhood caries and its prevention and management - Levesque, Joshua; Ghotra, Suhird; Mittermuller, Betty-Anne; DeMaré, Daniella; Lee, Victor H. K.; Cruz de Jesus, Vivianne; Olatosi, Olubukola O.; Alai-Towfigh, Hamideh; Schroth, Robert J. (Frontiers in Oral Health, 2024)
Introduction The Canadian Dental Association (CDA) recommends children visit a dentist within 6 months of the eruption of their first tooth or by 12 months of age. The aim of this study was to investigate Canadian dentists’ awareness and views on early childhood caries (ECC) and its prevention and management. Methods This study analyzed a subset of questions relating to dentists’ knowledge of ECC and prevention strategies, from a national survey of general and pediatric dentists, commissioned by the CDA in 2013. Analyses included descriptive, bivariate, and multivariate analyses. A p-value of ≤0.05 was considered significant. Results Three thousand two hundred thirty-two out of 14,747 dentists responded (response rate of 21.9%), with 95.1% having heard of ECC. Overall, 60.9% of respondents reported that they were comfortable providing treatment to children with ECC. Significant differences were found between the number of years in practice and whether dentists were or were not comfortable providing prevention (19.5 ± 12.6 years vs. 25.4 ± 12.1 years; p < 0.001) or treatment for patients with ECC (19.1 ± 12.7 years vs. 22.5 ± 12.3 years; p < 0.001). Pediatric dentists (OR = 6.92; 95% CI: 2.57, 18.61), female dentists (OR = 1.13; 95% CI: 1.03, 1.24), dentists practicing in smaller urban areas (OR = 1.17; 95% CI: 1.07, 1.28), and dentists who were aware of the CDA's position on ECC (OR = 1.26; 95% CI: 1.13, 1.41) were more likely to be comfortable providing treatment for children with ECC. Conclusions While the majority of Canadian dentists have sufficient knowledge of ECC, not all are comfortable providing oral health care services to children at a young age. It is encouraging however, that most dentists are wanting additional oral health resources designed for education on ECC prevention for parents of young children.